Evaluasi Sensori Kaldu Cair dari Limbah Tulang Ayam dengan Penambahan Lemak Ayam Menggunakan Presto - Herliana, Fitri; Putri, Destiana Adinda (Universitas Bumigora, 2025)
Chicken bone by-product is one of the product waste generated from the chicken processing industry, which is often considered as a worthless waste. However, chicken bones contain various important nutrients such as protein, calcium, and collagen. So that chicken bones can be utilized to become chicken bone broth. The addition of chicken fat to chicken bone broth is expected to affect the color, aroma, taste, and viscosity of chicken bone broth. This study aims to determine the composition of chicken bone broth that is preferred and accepted by many people.The method used in this research is Factorial Randomized Complete Design (CRD) with the first factor is the addition of fat to the broth boiling with 0%, 5%, and 10% fat concentration, the second factor is the length of boiling time, namely 30 minutes and 60 minutes with 3 repetitions, so there are 6 treatments, namely A1B1 = 0% fat:time 30 minutes, A1B2 = 0% fat: time 60 minutes, A2B1 = 5% fat: time 30 minutes, A2B2 = 5% fat: time 60 minutes, A3B1 = 10% fat: time 30 minutes, A3B2 = 10% fat: time 60 minutes. The results shows that the more fat added in the boiling process, the more favorable it is and the longer the boiling process, the more favorable it will be. So the process of adding fat and the length of boiling affect the level of liking in the aspects of aroma, color, taste, and viscosity of chicken bone broth. This research is expected to contribute to the development of sustainable waste treatment technology, as well as increase awareness of the importance of waste utilization in the food industry.